An Assessment of the ‘Lawfulness’ of Use of Force as Dispute Settlement Method - Rahman, Md Mustakimur; Tushi, Mohsina Hossain (Faculty of Law, Universitas Brawijaya, 2019)
Public international law has been developing and working with international humanitarian law & international human rights law together. As it developes, international law is renovating its nature from softer to harder. Although it is a great achievement to see that international (criminal) law has the influence to deal with some particular international criminals, however, the world is still far beyond from its ambition. Sometimes states are behaving very unusual against other states and using force for various reasons. While using force against other states is prohibited under Article 2(4) of the UN Charter. Nevertheless, states can use force under Article 51 if it is necessary for self-defence and only if it is approved by the Security Council under Chapter VII of the UN Charter. However, it is a question of fact that how a state can use force(s) and how it will be legitimate under several international laws? Hague law prohibits the use of new weapons and engine in the war because it seems disproportionate and unnecessary while the UN Charter is silent about the method of using force. Hence, it seems not clear that how a ‘force’ would be measured and will pass the ‘legality’ test. The indicator, thus remain unclear and very subjective.